ANALISIS PERILAKU MASYARAKAT DALAM PENGELOLAAN LINGKUNGAN DISEPANJANG DAERAH ALIRAN SUNGAI BATANG KURANJI (Universitas PGRI Sumatera Barat, 2011)
The behavior is activity, personal action or measure for environmentbecome habit and appear it because reciprocal relationship between human andenvironment. Based on law No.23 in 1997 about environment management, article5 explain that everyone has rights to role in environment management and duty toprotect environment conservation. A ware that reciprocal relationship betweenhuman and environment to protect environment as for as stream flow (DAS) and itstill continue needs human demanded form wise measure who lives around steamflow for human matrealized as environment builder and control resourcesadvantage on wise.This research was did in upper course of river, center and down streamBatang Kuranji consist of Lambung Bukit village, Kalumbuk and Kurao Pagangon july until october 2006. This research was did with short survey, data raisingmethod include primer and secondary data. Data analys was used measuringcommunity behavior which did with quantitative method, double regressionanalys and continue F-test (varian analys) also t-test (partial analys).The result of research was showed that community behavior inenvironment management belong to medium and not good which include farmingactivity, extractive mining-c and domestic trash management. While factors areinfluence behavior consist of understanding high environment, low category ofgovernment commitment and kind of work category with realm connected.